Authenticity as a Resilience Factor Against CV-19 Threat Among Those With Chronic Pain and Posttraumatic Stress Disorder - Reed, David E.; Lehinger, Elizabeth; Cobos, Briana; Vail, Kenneth E.; Nabity, Paul S.; Helm, Peter J.; Galgali, Madhwa S.; McGeary, Donald D. (Frontiers in Psychology, 2021)
Objective: The novel coronavirus (2019; CV-19) is linked to increases in emotional distress and may be particularly problematic for those with pre-existing mental and physical conditions, such as chronic pain and posttraumatic stress disorder (PTSD). However, little empirical research has been published on resilience factors in these individuals. The present study aims to examine authenticity as a resilience factor among those with chronic pain and/or PTSD. Methods: Prior to the national response to the pandemic (January 10-24, 2020), participants were screened for pain-related disability (Oswestry Disability Index; ODI) and PTSD symptoms (Posttraumatic Checklist for DSM-5; PCL-5), and on the basis of those responses were categorized into one of four groups: healthy, chronic pain only, PTSD only, or comorbid chronic pain and PTSD. During the CV-19 pandemic (May 5-May 13, 2020), participants responded again to the ODI and PCL-5, in addition to the Wood Authenticity Scale, Brief Pain Inventory, and items related to the CV-19 pandemic. Results: A total of 110 participants (54.55% women), aged 42.19 (SD = 13.16), completed the survey during the pandemic. The comorbid group endorsed higher levels of CV-19 Threat and Impact compared to all other groups. Authenticity moderated this relationship relevant to CV-19 Threat among those in the chronic pain only group, and not in any other group. Conclusions: The comorbid group endorsed higher levels of CV-19 Threat and Impact compared to all other groups. Importantly, greater authenticity was associated with less CV-19 Threat in the chronic pain only group, and not in any other group. The present study also highlights the importance of engaging authentically for those with chronic pain during the pandemic.